2020
DOI: 10.1093/nar/gkaa484
|View full text |Cite
|
Sign up to set email alerts
|

RaptRanker: in silico RNA aptamer selection from HT-SELEX experiment based on local sequence and structure information

Abstract: Aptamers are short single-stranded RNA/DNA molecules that bind to specific target molecules. Aptamers with high binding-affinity and target specificity are identified using an in vitro procedure called high throughput systematic evolution of ligands by exponential enrichment (HT-SELEX). However, the development of aptamer affinity reagents takes a considerable amount of time and is costly because HT-SELEX produces a large dataset of candidate sequences, some of which have insufficient binding-affinity. Here, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…The continuous motif indicated that the sequences in the data had the preference for specific subsequences. The result was partly consistent with our previous research [20] that implied…”
Section: S14 Sequence Logo Mapsupporting
confidence: 94%
See 1 more Smart Citation
“…The continuous motif indicated that the sequences in the data had the preference for specific subsequences. The result was partly consistent with our previous research [20] that implied…”
Section: S14 Sequence Logo Mapsupporting
confidence: 94%
“…The SPR assays were performed using a Biacore T200 instrument (GE Healthcare) as described previously with slight modifications [20]. BO uses both the search for sequences that have not been explored to a reasonable extent and the utility of utilizing sequences with known affinity to select the next sequence for evaluation.…”
Section: Surface Plasmon Resonance (Spr) Assaymentioning
confidence: 99%
“…Conventional loop accessibilities on single structure succeeded in the analysis and prediction of RNA-binding proteins and the in silico RNA aptamer selection on HT-SELEX (79,80). There is a possibility that the loop accessibilities proposed in this study have a broader range of impactful applications, as with the conventional accessibilities.…”
Section: ! "mentioning
confidence: 89%
“…RaptRanker [ 46 ] also carries out complex data analysis. In the first stage, it passes all sequences through a rough filter, however, they must exactly match in length and in the sequence of constant regions.…”
Section: Processing Of Hts Datamentioning
confidence: 99%
“…The extracted motifs can be further clustered to achieve more precise aptamer identification. No systematic comparison of different strategies and software solutions for candidate aptamer identification is available at the moment; however, in certain cases, research articles devoted to the development of particular bioinformatics tools describe a comparison to other similar instruments [ 23 , 24 , 46 ].…”
Section: Processing Of Hts Datamentioning
confidence: 99%